Regional environmental impacts on growth traits and phytochemical profiles of Glycyrrhiza glabra L. for enhanced medicinal and industrial use - Ghasem Eghlima; Yasaman Mashhadi Tafreshi; Fateme Aghamir; Hamid Ahadi; Mehrnaz Hatami (BMC Plant Biology)
Abstract Identifying the optimal cultivation regions and evaluating the impact of environmental factors are crucial for selecting the best conditions for the commercial production of important medicinal and industrial plants. This study examined the effects of different cultivation areas-Rayen, Eghlid, Kalat, and Zanjan-on the agro-morphological and phytochemical traits of Glycyrrhiza glabra. The findings revealed that the location where the plants were grown significantly influenced their physical and chemical characteristics. The Kalat region produced the tallest plants, measuring 96.86 cm, along with the highest shoot dry weight at 205.17 g, root dry weight of 318.00 g, root yield of 1590.12 g/m², and glabridin content of 2.92 mg/g dry weight (DW). Conversely, samples from the Rayen region had the highest glycyrhizic acid content at 17.92 mg/g DW and liquritigenin content at 1.22 mg/g DW. The Eghlid region showcased the highest total phenol content and antioxidant activity. Additionally, the study found a negative and significant correlation between altitude and glabridin content, indicating that glabridin levels decrease with increasing altitude. Based on the needs of the food and pharmaceutical industries, the study recommends the Rayen region for the production of glycyrhizic acid, the Kalat region for glabridin, and the Eghlid region for phenolic compounds.